GVHD after CAR T-cell therapy post allogeneic hematopoietic cell transplantation — successfully treated by extracorporeal photopheresis - Farid, Kiavasch Mohammad Nejad; Bug, Gesine; Schmitt, Anita; Lang, Fabian; Schubert, Maria-Luisa; Haberkorn, Uwe; Müller-Tidow, Carsten; Dreger, Peter; Schmitt, Michael (Frontiers in Immunology, 2024)
IntroductionCAR T-cell therapy is highly effective, but also associated with unique toxicities. Because of the origin of T cells in patients who previously underwent allogeneic hematopoietic cell transplantation (alloHCT), graft-versus-host disease (GVHD) in the post-CAR T-cell setting poses a relevant concern but is only scarcely studied. Potential risk factors and mitigation strategies (from CAR T-cell modifications to clinical management) are yet to be determined.MethodsSharing our retrospective experience and a mini-review of the literature, our aim is to better understand the frequency and risk of the potential occurrence of GVHD after CAR T cells, which are most likely underestimated. ResultsHere, we present a cohort of 11 patients with symptoms suggestive of GVHD out of 25 allografted patients treated with CAR T cells, of whom 3 patients (12%) had GVHD most likely triggered by the preceding CAR T-cell treatment. Severe chronic pulmonary GVHD occurred in a patient after CD19-directed CAR T-cell therapy. Extracorporeal photopheresis (ECP) mediated successful long-term control of GVHD without causing relapse of the underlying disease. Discussion/ConclusionIn conclusion, CD19-directed CAR T-cell therapy seems to be feasible in patients after alloHCT but might comprise the potential risk of triggering GVHD, most likely depending on the T-cell source, donor compatibility, and the specific CAR construct used.